Irrigation and fertigation scheduling effect on phenology and yield of spring sugarcane (Sachharum officinarum) - Singh, Hari; Singh, R K (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted at Agricultural Research Farm, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi to evaluate better irrigation water supply with nitrogen fertilization scheduling option to achieve maximum yield of spring planted sugarcane (Sachharum officinarum L.). Experiment was laid out in split plot design. The treatment consisted of three irrigation methods, viz. flood, furrow and drip; five nitrogen scheduling, viz. farmers practice, 4 splits, 6 splits, 8 splits and 10 splits. Results of the study indicated that higher number of tillers, leaf area index, number of millable canes and cane stalk yield were found under drip irrigation as compared to flood and furrow irrigation. Drip irrigation increase 22.30% cane stalk yield than irrigation through flood method. Significantly highest phenological growth, yield attributing characters and cane stalk yield were recorded with 6 splits of nitrogen application. Nitrogen application through farmers practice reduced 8.83 and 9.56% cane yield during two consecutive years, respectively. The overall effect of nitrogen application scheduling was in the order of 6 splits > 8 splits >10 splits >4 splits >farmers practice.